2014
DOI: 10.1111/tid.12234
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis caused by Blastomyces dermatitidis in a kidney transplant recipient: case report and literature review

Abstract: Blastomyces dermatitidis is a dimorphic fungus endemic to the midwestern, south-central, and southeastern United States known to cause disseminated infection in immunocompromised individuals. We report a case of B. dermatitidis peritonitis in a renal allograft recipient with new-onset ascites and cytomegalovirus encephalitis. Peritoneal blastomycosis is a rare clinical entity and, to our knowledge, this patient represents the first known case of peritoneal blastomycosis in a solid organ transplant recipient. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…B. dermatitidis can infect nearly every organ of the body including the eye, endocrine glands, muscles, peritoneum, and breast. 82,83 It is because of the great variety of clinical manifestations that B. dermatitidis infection has been called "the great pretender." As noted previously, more than half of infected patients are asymptomatic.…”
Section: Clinical Presentation Of Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…B. dermatitidis can infect nearly every organ of the body including the eye, endocrine glands, muscles, peritoneum, and breast. 82,83 It is because of the great variety of clinical manifestations that B. dermatitidis infection has been called "the great pretender." As noted previously, more than half of infected patients are asymptomatic.…”
Section: Clinical Presentation Of Human Diseasementioning
confidence: 99%
“…Tubo-ovarian abscesses can be complicated by extension of B. dermatitidis into the abdominopelvic cavity resulting peritoneal and omental nodules along with new onset ascites. 83…”
Section: Osseous Blastomycosismentioning
confidence: 99%
“…Thirty-one cases of blastomycosis were reported [ 7 , 8 , 13 , 20 , 21 , 23 , 35 , 45 , 46 , 48 , 51 , 52 , 55 , 59 , 60 , 64 , 65 , 67 , 68 , 70 , 195 , 209 , 211 , 244 ]. The majority of reports from the United States (10 of 16) were within endemic areas [ 20 , 21 , 35 , 45 , 46 , 51 , 60 , 67 , 195 , 211 ].…”
Section: Resultsmentioning
confidence: 99%
“…On review of 11 reported cases of blastomycotic peritonitis, six had definite pneumonia and three had antecedent pulmonary infection (pleural thickening, pleural effusion) . Blastomyces peritonitis has also been reported in a kidney transplant recipient …”
Section: Discussionmentioning
confidence: 99%